Association of Awareness in Medical and Dental Students regarding Adverse Effects of Smoking on Periodontal Health - Syeda Lalarukh Saba Shah, Nazli Shujaat, Mariam Fatima (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To study the association of awareness in medical and dental students regarding the adverse effects of smoking on periodontal health. Methodology: A data was gathered from 290 college students through a simple random sampling technique by using a Cross-sectional study. The questionnaire was split into two sections where data on demographics and questions on knowledge of the effect of smoking on periodontal health were gathered from the participants. The study was started after getting institutional ethical approval. All participants verbally consented, and confidentiality was maintained. A p-value of 0.05 was regarded as significant, with a confidence interval of 95%. The Chi-square test with SPSS version 26 was used to examine the statistical significance of various associations. Results: A total of 290 students completed the questionnaire and out of which 140(48.3%) were BDS students while 150 (51.7%) were MBBS students. The results obtained on awareness regarding the effects of smoking on periodontal health showed that gum diseases (0.003), halitosis (0.010), delayed wound healing (0.009), altered taste sensation (0.001), Oral cancer(0.013), mouth ulcers (0.036) were significantly associated with the use of smoking. The results emphasized to conduct anti-smoking awareness in students by conducting oral health education programs to persuade individuals to give up the smoking habit as many of the students were not willing to quit smoking despite knowing the harmful effects of smoking. Therefore, use of tobacco must be banned and it should be addressed at primary preventive level with a focus on quitting the tobacco which will further reduce the disease burden on the healthcare system related with smoking. Conclusion: There was a significant association between awareness regarding the effects of smoking on periodontal health which showed that gum diseases, halitosis, delayed wound healing, altered taste sensation, oral cancer, and mouth ulcers are related to smoking. Keywords: Oral Cancer, Gum disease, Mouth ulcer, Awareness, Halitosis, Tobacco, Smoking, Periodontal health.